Capacity Building Kelembagaan Komisi Informasi Provinsi Lampung dalam Meningkatkan Penyelenggaraan Keterbukaan Informasi Publik di Provinsi Lampung - Wice Yolanda; Noverman Duadji; Simon Sumanjoyo Hutagalung (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2020)
Transparency in government management is important to continue to be improved. The existence of a good government management is the increasing of public trust through public information disclosure. The Information Commission as an implementor in the implementation of law No. 14 of 2008 on Public Information Disclosure must continue to develop the capacity of institutions in order to provide maximum performance so as to encourage the implementation of public information disclosure in Lampung Province. This research aimed to describe the institutional capacity building efforts conducted by the Lampung Provincial Information Commission as well as identify inhibitory factors in the effort. The research method used a qualitative approach. The results of the study generally showed that the Lampung Provincial Information Commission began to make institutional capacity building efforts through the development of physical resources, the development of operational processes, and the development of human resources. Overall all three aspects have gone pretty well.Aspects of physical resource development are starting to go well due to structural changes in the institution that have a good impact on other aspects. In terms of operational development, efforts are made that motivate employees through incentives, personnel addition and building good cooperation and coordination. Aspects of human resource development are trying to be built through training efforts. The obstruction factor in capacity building efforts found to be related to legal devices as well as agency budgets that are not yet fully independent.